TRANSFORMASI TUTUR TARU PRAMANA KE DALAM FRAGMENTARI SOLAH TUTUR TARU PRAMANA - Pradnyawati, Ni Ketut Sukma; Suarka, I Nyoman; Kurniawan, Putu Widhi (Sphatika: Jurnal Teologi, 2025)
Tutur Taru Pramana is one of the classical manuscripts that tells the story of various types of plants that can be used as herbal medicine. Essentially, Tutur Taru Pramana is an oral narrative text that describes dialogues between characters within the text, such as the character Sang Prabhu Mpu Kuturan, a powerful healer who possesses the knowledge to communicate with plants. This study aims to examine the transformation of oral literary works into a fragmentary performance art, as a form of adaptation and modification of literary works into a performance medium. Data collection was conducted through reading, translation, and observation methods, using techniques such as note-taking, direct translation, transcription, and interviews. The data were analyzed using a qualitative method supported by descriptive-analytical techniques and examined through Sapardi Djoko Damono's theory of transformation or intersemiotic transfer. The results of the analysis are presented using both formal and informal methods, through deductive and inductive techniques. The findings of this study reveal the transformation process of Tutur Taru Pramana into the performance Fragmentari Solah Tutur Taru Pramana, which involves reduction, adaptation, and modification. The results of this research are expected to serve as a reference for similar studies and to foster gratitude for the environment, empathy toward others, and efforts to maintain the balance of plant ecosystems.